POSSIBILITIES OF COMPUTED TOMOGRAPHY IN THE DIAGNOSIS OF PRIMARY PULMONARY VASCULITIS - I. A. Sokolina; I. M. Koroleva (Вестник рентгенологии и радиологии)
Objective: to study the main computed tomography (CT) signs of primary pulmonary vasculitis at different stages of disease development. Material and methods. Eighty-nine patients, including those with Wegener’s granulomatosis (WG) (n = 60), Churg–Strauss syndrome (CSS) (n = 24), or microscopic polyangiitis (MPA) (n = 5), were examined. Vasculitis was diagnosed on the basis of comprehensive clinical, X-ray, and morphological examination. CT study was performed in 40 (85.1%) patients over time. Radiography encompassed chest X-ray and computed tomography. Results. The CT signs of WG were as follows: parenchymal infiltrates in 41 (68.3%) patients, vast zones of ground glass and consolidation in 16 (21.6%), and bronchial wall thickening in 27 (46.7%). The infiltrates showed aseptic decay cavities in 26 (63.4%) cases. In CSS, the CT changes included ground glass symptom (100%), consolidation symptom (54.2%), bronchial wall thickening concurrent with bronchial dilatation (87.5%), and increased peripheral pulmonary vessel diameter (45.8%). CSS was typified by migratory infiltrates. The pulmonary manifestations of MPA were characterized by the regions of alveolar infiltration of varying intensity and extent. Conclusion. The use of CT in pulmonary vasculitis makes it possible to reliably detect and differentiate pathological changes in the lung, to estimate their extent and monitor the efficiency of treatment.